385Prospective associations between serum homocysteine, folate, vitamin B12 and risk of metabolic syndrome. (2nd September 2021) - Woo, Hye Won; Shin, Min-Ho; Kim, Yumi; Choi, Bo-Youl; Kim, M-iKyung
Abstract: Background: Both elevated homocysteine (Hcy) and metabolic syndrome (MetS) are associated with cardio-metabolic disease. However, the potential causality in the association between Hcy and MetS is unclear, and there is uncertainty about the importance of serum level of folate and vitamin B12 for MetS. The aim of this study was to determine the prospective associations between serum homocysteine, folate and vitamin B12, and incidence of MetS in a community-based cohort of Korean adults aged ≥ 40 years. Methods: We measured serum Hcy, folate and vitamin B12 in 2, 895 participants (1, 187 men and 1, 708 women) who did not have MetS. During follow-up (10, 043 person-years), 471 MetS cases were newly diagnosed. Results: Higher Hcy levels were positively associated with risk of MetS (adjusted incidence rate ratio, IRR 1.87; 95% CI, 1.07–3.25 for ≥15 compared with <10 μmol/L of Hcy in men; IRR 1.81; 95% CI, 1.06–3.08 for ≥10 compared with <5 μmol/L of Hcy in women). However, serum folate was not associated with MetS, and higher serum vitamin B12 levels were associated with a statistically significant protection of MetS in men only (IRR 0.61; 95% CI, 0.42–0.90; P for trend=0.0082 in the highest tertile). Conclusions: Hcy levels were positively associated in men and women, and serum vitamin B12 was inversely associated with risk of MetS in men but not in women. Serum folate do not seem to be a protective marker for MetS. Key messages: Our results extend previously reported associations of Hcy with MetS, and the absence of associations of folate with MetS.